Significant alterations in peripheral lymphocyte subsets and immune-related protein profiles in patients with periprosthetic joint infection - Li, Zhuo; Yang, Fan; Fu, Jun; Li, Zhi-Yuan; Hao, Li-Bo; Yuan, Lin; Chen, Ji-Ying; Xu, Chi (Frontiers in Immunology, 2025)
PurposeWhile local immune responses in periprosthetic joint infection (PJI) are increasingly studied, systemic immune alterations remain poorly characterized. Therefore, this study aimed to investigate the change in peripheral lymphocyte subsets and immune-related protein profiles in patients with PJI, and explore the potential value of these indicators for the diagnosis of PJI.MethodsBetween July 2023 and January 2024, this prospective study recruited 82 patients who had been diagnosed with PJI or aseptic failure (AF), or who were healthy controls. Peripheral blood lymphocyte subpopulations and immune-related proteins were measured using flow cytometry or nephelometry and compared between groups. The diagnostic capability of different indicators for PJI was assessed. Besides, candidate markers were validated in an independent prospective cohort.ResultsCompared with the AF group, the proportion and absolute counts of natural killer (NK) cells in the PJI group were significantly higher, while those of B cells were lower. Differences in most immune-related proteins were observed between PJI and AF cases. Of them, the haptoglobin was the most notably increased in the PJI group than in the AF group (245.08 ± 99.00 mg/dl vs. 108.22 ± 52.37 mg/dl, P < 0.001), which exhibited the best diagnostic performance with an area under the curve (AUC) of 0.890.(95% CI, 0.803-0.978). When haptoglobin was combined with C-reactive protein (CRP), the AUC for the diagnosis of PJI increased to 0.937 (95% CI, 0.876-0.998). No significant differences were observed between the AF and primary total joint arthroplasty (TJA) groups regarding these immune-related indicators. In addition, the diagnostic efficacy of haptoglobin was validated in an independent cohort.ConclusionsThe systemic immune dysregulation observed in PJI patients can lay the foundation for further in-depth understanding of the immune response in PJI. The immune-related markers demonstrated promising value in diagnosing PJI, especially when synovial fluid was unavailable. Multicenter validation was warranted to confirm clinical utility.